Assessing energy expenditure in male endurance athletes: validity of the SenseWear Armband - Koehler, K.; Braun, H.; de Marees, M.; Fusch, G.; Fusch, C.; Schänzer, W. (Medicine & Science in Sports & Exercise, 2011)
Purpose: The correct assessment of energy expenditure (EE) in athletes is important to ensure that dietary energy intake is sufficient. In general, athletes are individuals with especially high levels of total EE (TEE) and exercise-related EE (ExEE). The SenseWear Pro3 Armband (SWA) is a multisensor device for the individual assessment of EE, but data on the validity for higher exercise intensities are missing. The aim of the study was to validate the SWA for the assessment of TEE and ExEE in endurance athletes. Methods: The SWA was worn by 14 male endurance athletes for 7 d during a regular training period, and TEE was measured in parallel with the doubly labeled water method. Two controlled exercise trials (treadmill running = 2.4-4.8 m·s-1, stationary bicycling = 140-380 W) were performed, during which indirect calorimetry was used to assess ExEE. Results: TEE assessed with the SWA and TEE measured with the doubly labeled water method were significantly correlated (r = 0.73, P < 0.01), but there were a proportional bias and considerably wide limits of agreement (-1368 to 1238 kcal·d-1). The error of TEE assessed with the SWA was related to the athletes' individual lactate thresholds (P < 0.05). During running and bicycling, ExEE was significantly underestimated for most exercise intensities, and the underestimation increased with exercise intensity (P < 0.001). Conclusions: According to our results, the SWA does not provide valid results of TEE and ExEE in endurance athletes because of the underestimation of EE at higher exercise intensities. It seems necessary to develop exercise-specific prediction equations to improve EE measurements in athletes.